Diritto animale, diritto degli animali e diritti degli animali. L’auspicio di un intervento riorganizzativo del legislatore tra esigenze sociali e necessità giuridiche di sistema (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article examines the most recent situations concerning animals law, trying to deepen the systematic inconsistencies which seem to underlie different interpretation difficulties, and attempting to outline the necessity of a general intervention of the legislator to completely regulate the matter.
Keywords: Animal law; Sentient beings; Animals; Movable property; Rights of animals